Unveiling the landscape of cruise tourism research: a bibliometric analysis and visualisation - Islam, Md. Tariqul; Pradhan, Biswabhusan; Haizan Nor, Rozi Nor; Ahmed Saleh, Rakib; Kumar, Jeetesh (Universiti Putra Malaysia, 2024)
Cruise tourism comprises having a vacation on a large passenger ship or boat, typically visiting several destinations along a predetermined itinerary, and it has taken the attention of academicians for the past two decades. This research study conducts a comprehensive longitudinal analysis of cruise tourism research covering 2003 to 2022. A meticulous selection process identifies 590 seminal articles from the Scopus database, which are then subjected to thorough bibliometric analysis. The R package (Bibliometrix R-package) is utilised to conduct the bibliometric analysis that incorporates various indicators to comprehend the overall trends in cruise tourism research, including annual output, top journal, prolific author, influential articles, author keywords, co-citations, and social structures. The analysis findings indicated that the United States and China emerged as the leading countries in cruise tourism research. Moreover, keywords like cruise tourism, cruise industry, cruise ships, cruise travel, and cruise experience appeared frequently, indicating their prominence within the domain. The insights gained from this analysis provide valuable strategic information for researchers, aiding them in developing and planning their future studies in cruise tourism.